2018
DOI: 10.1073/pnas.1811962115
|View full text |Cite
|
Sign up to set email alerts
|

Birth delivery mode alters perinatal cell death in the mouse brain

Abstract: Labor and a vaginal delivery trigger changes in peripheral organs that prepare the mammalian fetus to survive ex utero. Surprisingly little attention has been given to whether birth also influences the brain, and to how alterations in birth mode affect neonatal brain development. These are important questions, given the high rates of cesarean section (C-section) delivery worldwide, many of which are elective. We examined the effect of birth mode on neuronal cell death, a widespread developmental process that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 68 publications
1
45
3
Order By: Relevance
“…Data from males and females were combined in all analyses. Previous studies from our lab found no sex differences in cell death during the time points analyzed here (Ahern et al, 2013;Mosley et al, 2017a;Castillo-Ruiz et al, 2018a;2018b). We, and others, also have not found sex differences in microglial number or morphology in newborn mice (Strahan et al, 2017;Hanamsagar et al, 2017;Castillo-Ruiz et al, 2018a), although such sex differences have been reported in rats (Schwarz et al, 2012;VanRyzin et al, 2019) and adult mice (Hanamsagar et al, 2017;Guneykaya et al, 2018;Villa et al, 2018).…”
Section: Statisticscontrasting
confidence: 56%
“…Data from males and females were combined in all analyses. Previous studies from our lab found no sex differences in cell death during the time points analyzed here (Ahern et al, 2013;Mosley et al, 2017a;Castillo-Ruiz et al, 2018a;2018b). We, and others, also have not found sex differences in microglial number or morphology in newborn mice (Strahan et al, 2017;Hanamsagar et al, 2017;Castillo-Ruiz et al, 2018a), although such sex differences have been reported in rats (Schwarz et al, 2012;VanRyzin et al, 2019) and adult mice (Hanamsagar et al, 2017;Guneykaya et al, 2018;Villa et al, 2018).…”
Section: Statisticscontrasting
confidence: 56%
“…Together with birth timing, other extrinsic factors also modulate cell death. For example, delivery mode (Castillo-Ruiz et al, 2018b) and the exposure to a microbiota at birth (Castillo-Ruiz et al, 2018a) affect the magnitude of cell death in the neonatal mouse brain. Moreover, effects are regionally specific in both cases, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This could be problematic, because tight temporal control is a basic feature of neural development (Durand and Raff, 2000;Rougvie, 2005;Moss, 2007), and disruptions can lead to developmental defects (Bateman and McNeill, 2004). Changes in the overall magnitude of neonatal cell death may lead to long-term changes in neuron number, as shown for effects of birth mode in mice (Castillo-Ruiz et al, 2018b). Because naturally-occurring cell death in the human brain is ongoing at birth (Lossi et al, 1998;Abrahám et al, 2001;Lavezzi et al, 2006;Abitz et al, 2007), it is possible that some of the reported effects of birth timing on child development (El Marroun et al, 2012;Abel et al, 2017;Heuvelman et al, 2018) are related to alterations in cell death, or a dissociation of cell death from other neurodevelopmental events…”
Section: Discussionmentioning
confidence: 99%
“…Now comes a report in PNAS from Castillo-Ruiz et al (1) that, in mice, cesarean delivery has a rather unexpected effect on brain development that is both profound and widespread. Using caspase-3 production to identify cells about to "give up the ghost", they surveyed naturally occurring cell death (apoptosis) in 13 different brain regions and carefully controlled for a variety of factors to compare development in cesarean-delivered versus vaginally delivered newborns.…”
mentioning
confidence: 99%
“…These results raise a host of questions about whether cesarean delivery has a similar effect in humans, subjecting newborns to a greater loss of brain cells and potential alterations in neonatal behavior that could have lifelong consequences. Castillo-Ruiz et al (1) cite several studies indicating an increased risk for autism and attention deficit hyperactivity disorder in cesarean-delivered babies, but point out that the studies are controversial, in large part, because of the difficulty in adequately controlling for all of the confounding factors that distinguish women who delivery vaginally versus by C-section. Hence, they examined the question in mice so that they could control for other factors to show unequivocally that the mode of delivery affects brain development.…”
mentioning
confidence: 99%